2014
DOI: 10.3892/ijmm.2014.1931
|View full text |Cite
|
Sign up to set email alerts
|

Natakalim improves post-infarction left ventricular remodeling by restoring the coordinated balance between endothelial function and cardiac hypertrophy

Abstract: Endothelial dysfunction can lead to congestive heart failure and the activation of endothelial ATP-sensitive potassium (KATP) channels may contribute to endothelial protection. Therefore, the present study was carried out to investigate the hypothesis that natakalim, a novel KATP channel opener, ameliorates post-infarction left ventricular remodeling and failure by correcting endothelial dysfunction. The effects of myocardial infarction were assessed 8 weeks following left anterior descending coronary artery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…En-dothelial cells regulate the functions of the cardiovascular system by secreting nitric oxide (NO), endothelin-1 (ET-1), prostacyclin (PGI 2 ), and other bioactive substances, which play important roles in the pathophysiology of heart failure [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…En-dothelial cells regulate the functions of the cardiovascular system by secreting nitric oxide (NO), endothelin-1 (ET-1), prostacyclin (PGI 2 ), and other bioactive substances, which play important roles in the pathophysiology of heart failure [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…We investigated the effects of both Ipt and Nat in PO-CHF and explored the effects of Nat in MI-CHF and ISO-CHF. Our results in the independent experiments indicated that both Ipt and Nat could restore endothelial function and improve PO-CHF, MI-CHF, ISO-CHF, and HCVR [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 65%
“…In our previous study, the effects of Ipt were observed in PO-CHF at doses of 1, 3, and 9 mg/kg, and Nat effect was observed in the PO-CHF and MI-CHF experiments. These results showed that both Ipt and Nat could significantly improve the hemodynamics, cardiac disorders, and cardiac remodeling, and could decrease the levels of atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) [7][8][9][10] . In the present study, we observed the effects of Nat at doses of 1, 3, and 9 mg/kg, and the results were in accordance with previously obtained results [7][8][9][10] .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations